Video atlas of ophthalmic suturing - Brooks, Steven E. (Thieme, 2018)
Video Atlas of Ophthalmic Suturing: Fundamentals and Techniques by Steven Brooks, MD, is the first multimedia atlas dedicated to effective suturing and knot tying skills in ophthalmic surgery. The text and videos not only cover essential suturing techniques, but merge these concepts with critical principles of wound healing, tissue biomechanics, ergonomics, and the physical properties of common ophthalmic sutures and surgical needles. This atlas fills a significant knowledge gap in educational ophthalmic surgery literature, and greatly enhances the fundamental knowledge and skills provided in.